Assessment of efficacy of platelet-rich plasma application in regeneration of the facial nerve in rabbits - Gardašević, Milka F.; Petković-Ćurčin, Aleksandra; Vojvodić, Danilo V.; Marjanović, Uroš; Djurdjević, Dragan; Jović, Saša; Vulović, Dejan; Matijević, Stevo (Vojnosanitetski pregled, 2023)
Background/Aim. The injuries of the facial nerve lead to paralysis of the mimic musculature, which is conditioned by functional disorders accompanied by deformity of varying degrees depending on the intensity and location of the injury. Surgical treatment is a method of choice to treat an injured nerve. Injuries in the parotid lodge area are repaired by direct neurosuture in combination with platelet-rich plasma (PRP). Methods. The experimental study was carried out on 48 chinchilla male rabbits (Oryctolagus cuniculus), of about the same weight (2,500–3,000 gr), aged between 3 and 4 months in two surgical stages, in two different periods – six and ten weeks after the first surgical procedure. The animals were divided into four groups: Group I (suture); Group II [suture and fibrin glue (FG)]; Group III (suture and PRP); Group IV (sutures, FG, and PRP). Each group had two subgroups based on the duration of the experiment (six and ten weeks). A part of the dissected nerve in the length of 5 mm was subjected to histologic verification, where the number of axons and Schwann cells was determined and expressed numerically based on the histological sample of the tissue of the observed nerve. The extent of the presence of connective tissue and the degree of neovascularisation is shown by the description of histological samples by grades (connective tissue 1-4, neovascularisation 1-3). Results. Our results showed that all parameters of regeneration of damaged nerve showed a significantly higher regeneration efficiency after six and ten weeks of intervention in groups treated with PRP therapy with or without using FG. Conclusion. The use of PRP and the stimulating effect of activated growth factors results in the regeneration of the facial nerve in the sense of replication of the Schwann cells and the number of axons, with a high degree of neovascularization and minimal proliferation of connective tissue, which histologically corresponds to a healthy nerve.
Keywords: animals, laboratory; facial nerve injuries; histological techniques; nerve regeneration; platelet rich plasma; rabbit